PKM Inovasi Permainan Matematika untuk Mengasah Kemampuan Berpikir Kritis Siswa SD: Pengabdian - Marselina Wali; Yohanista Sabina Deda; Kristoforus Jegaut Kabut; Lusia Genereng Lasar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This PKM activity aims to develop the critical thinking skills of elementary school students through mathematical game innovations. The method used is a combination of demonstration methods carried out by PGSD students and direct play methods carried out by elementary school students. The approach used is a collaborative approach. The activity is carried out in an open environment, namely in the Koni field in the afternoon, in order to create a more comfortable, enjoyable, contextual playing atmosphere, and is able to arouse high curiosity from students who are involved in this PKM activity. This activity involves all elements of education implementers, namely lecturers, students, and elementary school students in community service activities that are educational and social in nature. The designed math games are adjusted to the needs and development levels of students, and integrate mathematical logic with elements of the surrounding environment. The results of this activity show that students are more active, enthusiastic, more motivated to learn mathematics and are able to understand mathematical concepts as a whole. In addition, the advantages of this PKM activity are strengthening social interaction, improving students' critical thinking skills, and building harmonious relationships between academic activities and the community.